PENGAWASAN IZIN OPERASIONAL KEBERADAAN INDOMARET DI KECAMATAN RUMBAI PESISIR OLEH DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU - Ratna Oktavianda; Hendry Andry (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
This study aims untyk know supervision of Industry and Trade of Pekanbaru in overseeing Operations Permit Indomaret presence in Sub Rumbai Coastal city of Pekanbaru. Monitoring indicators used include preliminary supervision, ongoing monitoring, feedback control is done by the Department of Industry and Trade of the city of Pekanbaru. This type of research that is located in the office of the Department of Industry and Trade of Pekanbaru is the descriptive method with qualitative data analysis, in line with the objectives of the research, the study population was Head of Industry and Trade, Head of Trade, Commerce and Metrology Business Section, Section of Supervision and Guidance , Indomaret Manager, Small and Medium Enterprise Communities that exist around Indomaret. To support the validity and research, then in charge of the population in the Office of Industry and Trade as many as 6 people, as many as 4 people Indomaret Manager and Small Business Community that is around Indomaret as many as 40 people. The sampling technique for the head of the Department and the staff of Department of Industry and Trade of Pekanbaru using sampling techniques or other terms is saturated census and for existing communities around Indomaret using purposive sampling technique. Types and data collection techniques consist of primary data collected by using questionnaire data and interviews and secondary data collected by observation and documentation which is the source of data and information and a description of the parties related to this research. Based on this analysis technique can be concluded that the presence of Operations Permit Monitoring Indomaret in District Rumbai Coastal works quite accomplished. Recommendations are necessary in the future to consider is the Department of Industry and Trade of Pekanbaru can perform intensive supervision on Operational Permit Indomaret existence.